Acute Presentation of Lumbar Spinal Stenosis Due to Ossified Ligamentum Flavum: The Possible Role of Spondylolisthesis. Issue 2 (April 2019) - Perna, Fabrizio; Geraci, Giuseppe; Mazzotti, Antonio; Stefanini, Niccolò; Panciera, Alessandro; Faldini, Cesare
Abstract : Case: A 64-year-old woman with a history of low back pain, presented with acute gait impairment and lower limbs numbness without any history of trauma. Imaging studies revealed ossification of the ligamentum flavum (OLF) at L4-L5 and concomitant spondylolisthesis. Decompression surgery with en-bloc removal including the laminae, the ossified ligamentum flavum, and the medial facet and posterior stabilization was performed resulting in complete immediate recovery. Conclusions: This report is the first to describe a case of an acute nontraumatic presentation of OLF associated with spondylolisthesis. OLF pathogenesis in still unknown, although several factors have been considered. According to the literature, operative treatment has demonstrated to be effective.